Stable tRNA halves can be sorted into extracellular vesicles and delivered to recipient cells in a concentration-dependent manner. Issue 8 (2nd August 2020) - Gámbaro, Fabiana; Li Calzi, Marco; Fagúndez, Pablo; Costa, Bruno; Greif, Gonzalo; Mallick, Emily; Lyons, Shawn; Ivanov, Pavel; Witwer, Kenneth; Cayota, Alfonso; Tosar, Juan Pablo
ABSTRACT: Extracellular vesicles (EVs) are cell-derived nanoparticles that act as natural carriers of nucleic acids between cells. They offer advantages as delivery vehicles for therapeutic nucleic acids such as small RNAs. Loading of desired nucleic acids into EVs can be achieved by electroporation or transfection once purified. An attractive alternative is to transfect cells with the desired small RNAs and harness the cellular machinery for RNA sorting into the EVs. This possibility has been less explored because cells are believed to secrete only specific RNAs. However, we hypothesized that, even in the presence of selective secretion, concentration-driven RNA sorting to EVs would still be feasible. To show this, we transfected cells with glycine 5ʹ tRNA halves, which we have previously shown to better resist RNases. We then measured their levels in EVs and in recipient cells and found that, in contrast to unstable RNAs of random sequence, these tRNA halves were present in vesicles and in recipient cells in amounts proportional to the concentration of RNA used for transfection. Similar efficiencies were obtained with other stable oligonucleotides of random sequence. Our results demonstrate that RNA stability is a key factor needed to maintain high intracellular concentrations, a prerequisite for efficient non-selective RNA sorting to EVs and delivery to cells. Given that glycine 5ʹ tRNA halves belong to the group of stress-induced tRNA fragments frequently detected in extracellular space and biofluids, we propose that upregulation of extracellular tRNA fragments is consequential to cellular stress and might be involved in intercellular signalling.